Collective wage agreements and the adjustment of workers and hours in German service firms - Ulrich Kaiser; Friedhelm Pfeiffer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2000)
There is a growing concern about collective wage agreement and employment dynamics in Germany. In this paper, evidence is provided on the way collective wage agreements affect the adjustment of working hours, employment and other production factors when firms from the service sector are faced with demand shocks. The estimation results indicate that collective wage agreements significantly influence firms' employment policies. Enrolments and the employment of free-lance collaborators are negatively affected while the probability of using short-term employment contracts as a reaction to demand shocks is positively influenced. No significant effect on the probability of dismissing workers has been found.
Keywords: J30; J50; C33; 330; collective wage agreements; demand fluctuations and adjustment costs; random effects ordered probit model; business-related services; Dienstleistungssektor; Unternehmensdienstleistung; Tariflohn; Tarifpolitik; Arbeitsnachfrage; Konjunktur; Anpassungskosten; Arbeitszeitflexibilisierung; Befristeter Arbeitsvertrag; Beschäftigungseffekt; Schätzung; Deutschland